(untitled) (European Bison Conservation Newsletter, 2008)
The paper summarises existing knowledge about occurrence of wild European bison in Slovakia and provides information about the restitution of European bison to NP Poloniny, Slovakia, prepared by State Nature Conservancy of SR and Large Herbivore Foundation. On the basis of obtained results from radio-tracking of a small herd of bison released to wild, in period from 10.12.2004 to 3.8.2008, the paper characterises also spatial activity, requirements of biotopes and their preference. Home range of this herd was 7824,10 ha, from it 6912,79 ha in summer and 2204,41 ha in winter. Most preferred biotopes were meadows and pastures in succession state (26,3% of observations) and forest type 4320 – Fagetum typicum (20,9 % of observations).